Sources of Economic Growth in East Asia : A Nonparametric Assessment - Khan, Mohsin (IMF Working Papers; Working Paper, 2002)
The conventional growth-accounting approach to estimating the sources of economic growth requires unrealistically strong assumptions about the competitiveness of factor markets and the form of the underlying aggregate production function. This paper outlines a new approach utilizing nonparametric derivative estimation techniques that does not require imposing these restrictive assumptions. The results for East Asian countries show that output elasticities of capital and labor are different from the income shares of these factors, and that the growth of total factor productivity over the period 1960-95 has been an important factor in the overall growth performance of these countries.